About Certain Philosophical-Legal And General-Theoretic Issues (Based On The Base Of The Textbook's Analysis For Higher Educational Institutions By Viatasław Nikolayevich Zhukov "Philosophy Of Law." M.: Mirfilosophy, Algorithm, 2019.- 559) - Vladimir Valentinovich Kozhevnikov (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The purpose of this review was an objective evaluation of the textbook "Philosophy of Law" by the Professor Zhukov Vyacheslav Nikolayevich. For the achievement of this purpose there are the following objectives: 1) to show the advantages of the presented work; 2) to draw the author 's attention to the shortcomings, they are concerning: A) inconsistency in the determining of the status of the philosophy of law; B) position of the dominance of the legal psychology over the legal ideology within the legal consciousness; C) often unwarranted identification of such concepts as legality and legitimacy; D) other provisions of work. The result. The author of this article concluded that, despite the shortcomings which may be controversial and debatable, the work of the Professor Zhukov Vyacheslav Nikolayevich deserves attention of students, teachers and scientists, who takes an interest in studying of the difficult problems on the philosophy of law.